Response to Sam Gill’s Article ‘What is Mother Earth? A Name, A Meme, A Conspiracy’ - Sundström, Olle (Journal for the Study of Religion, Nature and Culture, 2024)
The author points out that Gill is clearly focused on disproving the historical existence of widespread ideas of a Mother Earth, and of the name Mother Earth and argues that this does not mean that the proper name Mother Earth is completely missing in ethnographic reports prior to Albrecht Dietrich’s Mutter Erdeand the Romanticists of the nineteenth century. The article explores two examples from ethnographies about the Sami people where terms that could reasonably be translated as "Mother Earth" are quite independent of a romantic image of ‘primitive‘ people.